Target Selection Signals for Arm Reaching in the Posterior Parietal Cortex - Scherberger, Hansjörg (J Neurosci, 2007)
The selection of visual stimuli as a target for a motor action may depend on external as well as internal variables. The parietal reach region (PRR) in the posterior parietal cortex plays an important role in the transformation of visual information into reach movement plans. We asked how neurons in PRR of macaque monkeys reflect the decision process of selecting one of two visual stimuli as a target for a reach movement. Spiking activity was recorded while the animal performed a free-choice task with one target presented in the preferred direction and the other in the off direction of the cell. Stimulus-onset asynchrony (SOA) was adjusted to ensure that both targets were selected equally often and the amount of reward was fixed. Neural activity in PRR was action specific for arm reaching and reflected the timing of the SOA as well as the selection of reach targets. In individual trials, activity was strongly linked to the choice of the animal, and, for the majority of cells, target selections could be predicted from activity in the stimulation or planning period, i.e., before the movement started. Many neurons were gain modulated by the fixation position, but gain modulation did not influence the target selection process directly. Finally, it was found that target selection for saccade movements was only weakly represented in PRR. These findings suggest that PRR is involved in decision making for reach movements and that separate cortical networks exist for target selection of different types of action.